2023
DOI: 10.1080/13621718.2022.2156715
|View full text |Cite
|
Sign up to set email alerts
|

Study of laser directed energy deposition of Inconel 625 and austenitic steel

Abstract: Functionally graded material (FGM) is an advanced material that illustrates the number of properties in a single component. To develop FGM, it is very important to study each component gradient separately to understand the properties and their behaviour. This paper presents the study of the properties of deposited blocks of the different gradients of Inconel 625 (IN625) and stainless steel 304L (SS304L) (25% IN625 + 75% SS304L, 50% IN625 + 50% SS304L, 75% IN625 + 25% SS304L, and 100% IN625) by a laser directed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…They studied the influence of wire electro discharge machining (WEDM) on deposited blocks, 21 influence of substrate on different gradient 22 and material characterization of deposited blocks. 23…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…They studied the influence of wire electro discharge machining (WEDM) on deposited blocks, 21 influence of substrate on different gradient 22 and material characterization of deposited blocks. 23…”
Section: Introductionmentioning
confidence: 99%
“…Very few works are reported in the fabrication of functionally graded SS304L/IN625. [20][21][22][23] Carroll et al 20 developed an FGM block of a square crosssection of 16 mm wide and 34 mm tall by 910 W YAG laser using the DED technique. They conducted experimental and thermodynamic studies on FGM and found the presence of (Mo,Nb)C secondary phase which is responsible for crack development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This special issue includes all aforementioned trends of progress through 19 original research articles [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The editors of STWJ invited active researchers from the AM and welding communities to contribute to this special issue.…”
Section: Introductionmentioning
confidence: 99%